3D printed hyperelastic "bone" scaffolds and regional gene therapy: A novel approach to bone healing. Issue 4 (11th January 2018) - Alluri, Ram; Jakus, Adam; Bougioukli, Sofia; Pannell, William; Sugiyama, Osamu; Tang, Amy; Shah, Ramille; Lieberman, Jay R.
Abstract: The purpose of this study was to evaluate the viability of human adipose‐derived stem cells (ADSCs) transduced with a lentiviral (LV) vector to overexpress bone morphogenetic protein‐2 (BMP‐2) loaded onto a novel 3D printed scaffold. Human ADSCs were transduced with a LV vector carrying the cDNA for BMP‐2. The transduced cells were loaded onto a 3D printed Hyperelastic "Bone" (HB) scaffold. In vitro BMP‐2 production was assessed using enzyme‐linked immunosorbent assay analysis. The ability of ADSCs loaded on the HB scaffold to induce in vivo bone formation in a hind limb muscle pouch model was assessed in the following groups: ADSCs transduced with LV‐BMP‐2, LV‐green fluorescent protein, ADSCs alone, and empty HB scaffolds. Bone formation was assessed using radiographs, histology and histomorphometry. Transduced ADSCs BMP‐2 production on the HB scaffold at 24 hours was similar on 3D printed HB scaffolds versus control wells with transduced cells alone, and continued to increase after 1 and 2 weeks of culture. Bone formation was noted in LV‐BMP‐2 animals on plain radiographs at 2 and 4 weeks after implantation; no bone formation was noted in the other groups. Histology demonstrated that the LV‐BMP‐2 group was the only group that formed woven bone and the mean bone area/tissue area was significantly greater when compared with the other groups. 3D printed HB scaffolds are effective carriers for transduced ADSCs to promote bone repair. The combination of gene therapy and tissue engineered scaffolds is a promising multidisciplinary approach to bone repair with significant clinical potential. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1104–1110, 2018.